Socio-legal implications of cross-border marriage among Muslims in Malaysia: an empirical evidence - Md Said, Muhamad Helmi; Md Hashim, Noraini; Abdul Hak, Nora; Wok, Saodah; Che Soh @ Yusoff, Roslina (2018)
Marriage is a sacred bond, a tie between a man and a woman. Such relationship is blessed by Allah as it is mentioned in the Quran and the tradition (Sunnah) of the Prophet (PBUH). The laws created by man are meant to streamline the conduct of marriage, apart from the already provided hukum laid down in Islam. However, there are people who tend to violate these laws due to their own ignorance and this violation affects the future of such marriage and as well other people who are attached to it. Cross-border marriage is a marriage without permission from the registrar of marriage in each States and its solemnisation can be contracted in Malaysia or outside Malaysia. The purpose of this study is to examine and analyse the differences between demographics information of respondents towards the implications of cross-border marriage among Muslims in Malaysia. The sample consists of four hundred respondents came from four regions in Malaysia. A survey-using questionnaire was the main method of collecting the data. To support the empirical evidence, the semi-structured interview has also been conducted in this study. The research reveals that even though the respondents aware about the implications of cross-border marriage, still it requires a new mechanism to control this type of marriage from continuing in the future as it affects the people who are attached to it especially the women and children.